(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2011)
Sudden death of an individual has interested the medical community since the first report of an unexpected death of the Greek soldier Pheldippides on completing a historic run from Marathon to Athens to deliver the message of victory over the Persians in 490 B.C. We report a case occurred when two trainees of CRPF died on 23 Aug 2010, after they were taken ill during training at the Opadila Mahadeo training centre of CRPF &Rapid Action Force in Allahabad. They were taking part in a 16 Km run which is a part of physical routine & mandatory for every trainee. They were identified as Surjit Rai of Vaishali district in Bihar &Sunil of Tamil Nadu. After they fell ill apparently due to severe dehydration and exhaustion they were rushed to SRN hospital in Alllahabad where they succumbed later. Overt or concealed diseases are responsible for sudden death of jawans in field. Physicians should be able to recognize clinical symptoms of potentially fatal conditions. This is the first step in preventing the rare, but tragic, occurrence of death among jawans Moreover, since the large majority of the diseases responsible for death due to CVS causes are hereditary, and are already evident in post-pubertal age, pre-participation screening should be applied to young jawans starting competitive amateur career. The efficacy of screening depends mostly on the experience and competence of visiting physicians, but a simple and low-cost protocol, consisting of a careful medical and familial history taking, a thorough physical examination, a rest ECG and, when possible, a stress ECG can identify a large number of subjects with potentially lethal diseases. Further investigation to screen out other causes must consist of full Blood profile, BT, CT, PT, ESR, Electrolytes level, LFT, CXR, PFT, Lipid Profile, USG abdomen &pelvic area (in female jawans).